Response of arid northeast Mexico to global climate changes during the late Pleistocene to the middle Holocene. Issue 11 (30th July 2019) - Roy, Priyadarsi D.; Vera‐Vera, Guillermo; Curtis, Jason H.; Sánchez‐Zavala, José L.; Quiroz‐Jiménez, Jesús David; Muthu Sankar, Gowrappan
Abstract: Anthropogenic global warming might cause expansion of the drylands and trigger socio‐economic challenges in the water‐deficit subtropical regions. Changes in hydroclimate during the intervals of variable global temperature over the recent geological past, however, could provide useful information about the possible responses of these arid ecosystems to the near future warmer conditions. We evaluated hydroclimates of two different parts of subtropical North America by generating new records of surface processes and regional vegetation from drought‐prone northeast Mexico and subsequently compared them with the paleoclimate of the central‐southern United States. Our study suggests that congruent changes occurred in both parts during 13.5–9.5 cal ka BP, an interval with no warm pool in the northern Gulf of Mexico. The precipitation and erosion responded to temperature‐modulated variations in positions of the Inter‐Tropical Convergence Zone (ITCZ). Conditions were wetter than today in the subsequent warmer interval ( 9.5–8.2 cal ka BP) with generally stable ITCZ and the highest summer insolation. Hydroclimate changes of both parts lacked congruency during 8.2–6.8 cal ka BP as the northern Gulf of Mexico began hosting a warm pool. Similar to the modern conditions, this warm pool might have modified trajectories of the tropical storms. Erosion and abundance of C3 plants decreased in northeast Mexico. Higher wetness in the Mississippi River Basin and the southern Great Plains during this interval suggested that the storms made landfall more frequently in the central‐southern United States. © 2019 John Wiley & Sons, Ltd. Abstract : Reconstruction of hydroclimates in two different parts of the subtropical North America in the recent geological past provided valuable information about how this region might respond to the future global warming. Consistent warm pool in the Gulf of Mexico during 8.2‐6.8 cal ka BP modified trajectories of the tropical storms and the northeast Mexico became more arid compared to central‐southern USA.